0536 Daytime Sleepiness and Physical Activity In Adults with Type 2 Diabetes And OSA Treated with CPAP. (12th April 2019) - Luyster, Faith; Shi, Xiaojun; Atwood, Charles; Sereika, Susan; Strollo, Patrick; Stansbury, Robert; Chasens, Eileen
Abstract: Introduction: The impact of continuous positive airway pressure (CPAP) on physical activity is unclear. Inadequately treated obstructive sleep apnea (OSA) due to CPAP non-adherence may lessen physical activity due to daytime sleepiness. The purpose of this secondary analysis was to examine the association of daytime sleepiness and physical activity among adults with type 2 diabetes and OSA receiving therapeutic and non-therapeutic doses of CPAP. Methods: The sample (N=66) was from an ongoing randomized clinical trial (R01-DK096028) in which participants were randomized to either active-CPAP or sham-CPAP. Participants' average age was 59.7±9.7 years with a mean BMI of 36.0±6.6; 55% were male and 23% were non-White. CPAP dose was calculated as mean minutes of therapeutic treatment over 12 weeks; sham-CPAP participants were coded as having 0 minutes of therapeutic CPAP treatment. Average CPAP dose of ≥4 hours/day was categorized as adequately treated (n=28) and CPAP dose of <4 hours/day was categorized as suboptimally treated (n=38). At baseline, 6 weeks, and 12 weeks, participants completed the Epworth Sleepiness Scale (ESS) and wore a BodyMedia SenseWear armband to assess average number of steps/day over one week. Change scores for the ESS and number of steps from baseline to 6 weeks and 12 weeks were calculated. Results: No significant differences in baseline characteristics including age, race, education, apnea hypopnea index, BMI, and A1C were found between the adequately and suboptimally treated groups. There were no significant correlations between changes in ESS and number of steps over 6 and 12 weeks in the adequately treated group; however, in the suboptimally treated group, there was a correlation between change scores on ESS and number of steps over 6 weeks (r=-0.34, p=0.04). Conclusion: For adults with type 2 diabetes with suboptimally treated OSA, worsening daytime sleepiness is associated with a decline in physical activity over the first 6 months of CPAP treatment. Further research examining the influence of CPAP on physical activity is needed in larger samples. Support (If Any): This study was funded by the National Institutes of Health (R01-DK090628).